2016
DOI: 10.1371/journal.ppat.1005832
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection Leads to Development of High Frequencies of Cytotoxic Virus-Specific CD4+ T Cells Targeted to Vascular Endothelium

Abstract: Cytomegalovirus (CMV) infection elicits a very strong and sustained intravascular T cell immune response which may contribute towards development of accelerated immune senescence and vascular disease in older people. Virus-specific CD8+ T cell responses have been investigated extensively through the use of HLA-peptide tetramers but much less is known regarding CMV-specific CD4+ T cells. We used a range of HLA class II-peptide tetramers to investigate the phenotypic and transcriptional profile of CMV-specific C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
139
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 83 publications
11
139
0
Order By: Relevance
“…Dual IFN-γ and TNF-α intracellular cytokine staining of Subject 10027’s PBMCs, which produced the largest IFN-γ ELISpot response to DYS, confirmed that the ELISpot responses originated from CD4s and not CD8s, and suggested that these inflated cells were likely polyfunctional (Fig. 2F), as previously reported (11, 35). …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Dual IFN-γ and TNF-α intracellular cytokine staining of Subject 10027’s PBMCs, which produced the largest IFN-γ ELISpot response to DYS, confirmed that the ELISpot responses originated from CD4s and not CD8s, and suggested that these inflated cells were likely polyfunctional (Fig. 2F), as previously reported (11, 35). …”
Section: Resultssupporting
confidence: 85%
“…gB-loaded endosomes are also secreted as immunogenic exosomes that stimulate CD4 + memory T cells (36, 37). In HLA-DRB1*07:01 (DR7 + ) persons, the most immunogenic gB epitope is the extremely conserved DYSNTHSTRYV (DYS) epitope that is recognized by cytotoxic, CX 3 CR1 + CD4 + T cells (11, 38). …”
Section: Introductionmentioning
confidence: 99%
“…lished (16,47,52); however, this analysis indicates that CD4 ϩ T cells specific for the other 5 proteins also possess this capacity. CMV-specific CD4 ϩ T cells from all the donors examined expressed a CD107a response to at least 1 of the 6 HCMV proteins.…”
Section: Figmentioning
confidence: 87%
“…Production of pro-inflammatory cytokines in turn activates p38 in T cells, inhibits T cell telomerase activity, and promotes loss of CD28 and T cell differentiation, further creating a vicious cycle of immunosenescence (Macaulay et al 2013). CMVspecific T cells are found to express high levels of CX3CR1, which binds to injuried vascular endothelium-expressing fractalkine, and the β2-adrenergic receptor, which permits rapid response toward stress (Pachnio et al 2016;van de Berg et al 2012). It is important to note that not all persistent virus infections result in terminally differentiated T cells.…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 99%